Strategy for Adapting to Climate Change and Conserving Biodiversity in the Bangladesh Sundarbans - Ortolano, Leonard; Sánchez-Triana, Ernesto; Ferdausi, Shakil Ahmed (Taylor and Francis, 2016)
The Bangladesh Sundarbans region is a difficult place to live and the region will become increasingly inhospitable over time. Sea level rise, cyclonic storms, and embankment failures are constant hazards and the biodiversity of the mangrove forest is being reduced. In addition, increased waterlogging and soil and water salinization pose serious threats to agriculture, a livelihood option for a majority of residents. Research was undertaken to answer the following question: what strategy could the Government of Bangladesh consider in order to enhance the security of inhabitants of the Bangladesh “Sundarbans Impact Zone (SIZ)” and conserve the biodiversity of the Sundarbans mangrove forest? The proposed strategy, which was based on data and analyses from a team of social and natural scientists and engineers, includes two central elements: incentives to encourage migration out of the SIZ successfully and measures to reduce dangers from natural hazards for inhabitants who choose to remain. In addition, the strategy includes measures to conserve biodiversity and actions to strengthen government agencies operating in the Sundarbans so that other elements of the strategy can be implemented effectively.